2015
DOI: 10.1002/aelm.201500146
|View full text |Cite
|
Sign up to set email alerts
|

Cation Size Effects on the Electronic and Structural Properties of Solution‐Processed In–X–O Thin Films

Abstract: The nature of charge transport and local structure are investigated in amorphous indium oxide‐based thin films fabricated by spin‐coating. The In–X–O series where X = Sc, Y, or La is investigated to understand the effects of varying both the X cation ionic radius (0.89–1.17 Å) and the film processing temperature (250–300 °C). Larger cations in particular are found to be very effective amorphosizers and enable the study of high mobility (up to 9.7 cm2 V−1 s−1) amorphous oxide semiconductors without complex proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…Most research has focused on quaternary oxides such as a-In-Ga-Zn-O or a-Zn-In-Sn-O given their technological appeal; [48,49,[51][52][53][54][55][56][57][62][63][64][65][66]68,69,73,74,76] only a few studies addressed the properties of ternary AOSs systematically. [67,85,86] Moreover, a comparison of the results available in the literature is likely to be inconclusive because the crystallization temperature depends strongly not only on the metal composition but also on growth conditions (such as oxygen partial pressure, postdeposition temperatures and times) as well as film thickness.…”
Section: Local Structure and Amorphization Efficiencymentioning
confidence: 99%
See 4 more Smart Citations
“…Most research has focused on quaternary oxides such as a-In-Ga-Zn-O or a-Zn-In-Sn-O given their technological appeal; [48,49,[51][52][53][54][55][56][57][62][63][64][65][66]68,69,73,74,76] only a few studies addressed the properties of ternary AOSs systematically. [67,85,86] Moreover, a comparison of the results available in the literature is likely to be inconclusive because the crystallization temperature depends strongly not only on the metal composition but also on growth conditions (such as oxygen partial pressure, postdeposition temperatures and times) as well as film thickness.…”
Section: Local Structure and Amorphization Efficiencymentioning
confidence: 99%
“…A systematic experimental and theoretical study of the amorphous indium oxide doped with group III metals, Sc, Y, and La, showed that the amorphization efficiency increases with the size of the ionic radius of the substituted cation. [67] The local structure comparison of the amorphous In-X-O with 20% substitution of X = Sc, Y, or La have revealed that scandium is too small to suppress the amount of InO 6 polyhedra and to prevent their clustering, whereas lanthanum is large enough to make the In-La-O samples fully X-ray amorphous-even with only 5% La doping in films processed at 300 °C. [67] While a theoretical calculation of the crystallization temperature in a-In-X-O is beyond the scope of this work, the above results of the MD liquid-quench simulations clearly illustrate that complex interplay between the local and medium-range structural preferences of both the host and the substitution metals must be taken into account in the search for efficient amorphizers.…”
Section: Local Structure and Amorphization Efficiencymentioning
confidence: 99%
See 3 more Smart Citations